Authority Over Whose Head? Did Paul Instruct Wives or All Women to Cover Their Heads (1 Corinthians 11:2–16)? - Callon, Callie (Harvard theological review, 2024)
There is no scholarly consensus on whether Paul’s mandates on head coverings were directed solely to married women or to all women in the Corinthian community. I suggest the discussion can be tentatively advanced by considering two factors that have not received the attention they warrant in conjunction with this passage: first, the presence of slaves in the community, and second, that the Genesis material which Paul alludes to in these verses was understood in some ancient thought as addressing the institution of marriage rather than creation. I propose that, in view of these considerations, it is more likely that Paul directed his exhortations towards free(d) married women.